Melting Heat Transfer Of A Hybrid Nanofluid Flow Towards A Stagnation Point Region With Second-Order Slip - Pop, Ioan Mihai; Waini, Iskandar; Ishak, Anuar (SAGE Publications Ltd, 2020)
This paper examines the behaviour of a hybrid nanofluid flow towards a stagnation point on a stretching or shrinking surface with second-order slip and melting heat transfer effects. Copper (Cu) and alumina (Al2O3) are considered as the hybrid nanoparticles while water as the base fluid. The governing equations are reduced to the similarity equations using similarity transformations. The resulting equations are programmed in MATLAB software through the bvp4c solver to obtain the numerical solutions. The results reveal that two solutions are possible for the shrinking case (Formula presented.), where the bifurcation of the solutions occurs in this region. Moreover, the heat transfer rate and the skin friction coefficient enhance with the rise of the melting parameter. Meanwhile, these quantities decrease for a smaller second-order slip parameter. The temporal stability analysis shows that only one of the two solutions is stable as time evolves.